A failed attempt to explain relative motion illusions via motion blur, and a new sparse version. (September 2022) - Bach, Michael
Visual patterns can evoke marked, even beautiful motion illusions even if they are static; eye movements in all likelihood serve as temporal modulators. This paper concentrates on Ouchi-type "relative" or "sliding" motion illusions. It outlines an eye-motion-evoked motion-blur hypothesis, which does not correctly predict the shift direction of maximal illusion. This failure led to a nearly new particularly simple stimulus: an arrangement of dashed lines that strongly evokes a relative motion illusion, the "orthogonal dotted lines sway." The latter is well explained by motion integration.